Metal Ions Leachables And Microstructure Of Fake Orthodontic Braces: An In Vitro Study - Ibrahim Alkurdi, Riyam Haleem (2022)
Fake braces are an artificial orthodontic device that are now gaining attention and becoming increasingly popular among teenagers and youths in Malaysia. It involves illegal practitioners with doubtful quality and standard of tools and materials which have not been sterilised. Therefore, this study aimed to assess the elemental changes and the microstructure of fake braces immersed in simulated body fluid (SBF) and artificial saliva (AS). Five different fake braces were immersed in SBF and AS at 37 ˚C, and one fixed orthodontic appliance was used as control. The elementary changes of fake braces were analysed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), and Scanning Electron Microscope Energy Dispersive X-ray Spectroscopy (SEM-EDX) was used to analyse the morphological changes of the braces, assessed at days 0, 1, 4, 7, 14, and 28. The data have been analysed by using One-way ANOVA with post-hoc Bonferroni with P<0.05 considered as statistically significant. After immersion in SBF, ICP-OES revealed Na, K, Mg, Ca, Mo, B, Pb, Al, and P ions released from fake braces samples had significant ions release compared to control samples. When immersed in AS, Na, K, Mg, Ca, Cu, Pb, and Al ions, have significant ions releasing fake samples.